THERMOCHEMICAL AND SPECTROSCOPIC PROPERTIES OF MOLECULES IN ASTROPHYSICAL INTEREST - HASSAN, HENAR SLEMAN (Fırat Üniveristesi, 2017)
Atom moleküllerin özellikleri, atom-molekül ve molekül-molekül çarpışmalarından elde edilir. Ayrıca moleküllerin öteleme hareketleri ve titreşim dönme hareketlerinin termo dinamiksel ve spektroskopik olarak incelenmesi de moleküllerin özelliklerini verir. Oriaon ve Herschel teleskopları ile çok sayıdaki astrofiziksel öneme sahip molekülün spektroskopik özellikleri incelenmiştir. Bu teleskoplar ile son zamanlarda iki atomlu moleküllerden çok atomlu moleküllere kadar bazı gözlemler yapılmıştır. Bu spektroskopik analizlerden çıkan sıfır nokta enerjisi ve tüneleme olayları gibi kuantum mekaniksel olaylar klasik olarak incelenememektedir. Bundan dolayı atom molekül etkileşmelerinde kuantum mekaniksel metotların uygulanması önem kazanmıştır. Moleküldeki atom sayılarının fazlalığına bağlı olarak gerçek yada yaklaşık metotların, Hartree Fock (HF) ve Density Function Theory (DFT) yada konfigürasyon etkileşmesi (CI) kullanılması dikkate alınır. Bu tez çalışmasında astrofizikte önemli olan C2H5, C2H6, NO3, CH3OCH2OO gibi moleküller ele alınacaktır. Moleküle bağlı olarak HF, DFT ya da CI metotları uygulanıp elektronik olarak ve ayrıca moleküllerin titreşim dönmelerinden kaynaklanan termodinamik özellikler hesaplanacaktır.

The properties of atom and molecules be obtained from atom-molecule or molecule- molecule collisions or from spectroscopic and thermodynamic analysis of ro-vibrational and translational motion of components of molecule. There have been many spectro- scopic analysis of Astrophysical molecules that observed every recently in parallel to the development of technology of Orion, Herschel telescopes etc . With these telescopes very recently many molecules from diatom to poly-atomic molecules was observed and investigated as a spectroscopic analysis. The outputs form all these spectroscopic analysis are consist of many quantum e¤ects like tunneling and zero point energies which are not possible to calculate by using the classical physics. That is why, it is important to implement quantum mechanical methods to atom-molecule or molecule- molecule interaction to calculate quantum mechanical quantities. Depending of the size of molecule (number of molecule) it is important to implement accurate or ap- proximate quantum methods to the system like Hartree fock (HF), Density Function Theory (DFT) or Con…guration Interaction (CI) and so on. Some of molecules which are important in Astrophysics interest, would be studied in this theses are C2H5, C2H6, NO3, CH3OCH2OO. Depending on the molecule quantum mechanical HF, DFT , CI, etc. theories will be implemented and thermodynamic quantities from contribution of transition, electronic motion, and ro-vibration motion have been calculated.
Astrofizik alandaki moleküllerin termokimyasal ve spektroskopik özellikleri
Keywords: Fizik ve Fizik Mühendisliği